Effect of Argumentation-Based Teaching on Students’ Understanding, Reasoning and Decision-Making Concerning Food Preservatives - Ari Widodo; Intania Zainul Nurul Huda; Diana Rochintaniawati; Riandi Riandi (Postgraduate, University of Mataram, 2023)
Misuse of food preservatives in the society is alarming that it is necessary to raise students’ awareness about the danger to their health. Educating children about healthy food requires more than just promoting understanding but more importantly practicing reasoning and decision making. This study analyses the impact of lessons designed to improve students’ understanding, reasoning, and decision making on the use of food preservatives. Participants of the study were 30 students of 7th grade junior high school taught by a teacher who has been trained on argumentation-based teaching strategies. During the lessons students were provided with dilemmatic cases that stimulate their thinking followed by discussion before finally making a decision. Data were collected prior and after the lessons using a three-tier test that require students to provide answers that consist of explanation, reason, and evidence. The study shows improvement of students’ understanding of the content, reasoning skills, and decision making. Moreover, the study also reveals that the majority of the students tend to view food preservatives from the usefulness side but ignore the danger. The findings suggest that argumentation-based teaching strategy results in students’ deeper understanding of the content, reasoning and decision-making skills. This study recommends that efforts to promote students’ awareness of food preservatives and healthy diet can be done through a systematic and well-planned teaching strategy that encourage students to reason and to think deeply about the positive and the negative sides of food preservatives